First Report of Anthracnose Caused by Colletotrichum siamense on Malania oleifera in Guangxi, China - Lin, Shanyu; Qin, Li-Ping; Huang, Jinling; Li, Hongguo; Lu, Xiuhong (Plant disease, 2025)
Malania oleifera Chun & S. K. Lee, endemic and restricted to southwest China, is an important oilseed tree (Wang et al. 2021). In September 2024, anthracnose symptoms were observed on 10% of one-year-old M. oleifera leaves in a nursery located at the Experimental Center of Tropical Forestry, Chinese Academy of Forestry in Pingxiang, Guangxi (22°7'32''N, 106°44'31''E). Initial symptoms appeared as small, irregular brown spots on the edge of the leaf. These lesions expanded to brown necrotic areas with dark brown edges. Eventually, the whole leaf developed extensive necrosis, leading to withering and abscission. Five symptomatic leaf samples were randomly collected from different plants for fungal isolation. Leaves were surface disinfected sequentially with 75% alcohol (10 s) and 2% NaClO (2 min) and rinsed three times in sterile distilled water. From the margin between diseased and healthy tissues, 3 × 3 mm segments were aseptically excised and plated on potato dextrose agar (PDA) plates at 28°C. In total, twelve Colletotrichum-like isolates were obtained after 3 days of incubation. The colonies exhibited white cottony aerial mycelium, turning light grey on the obverse with orange conidial masses, and dark grey on the reverse. Conidia were hyaline, cylindroid to clavate, with both ends obtusely rounded, and measured (14.50 ± 1.48) μm × (4.69 ± 0.34) μm and (14.52 ± 1.03) μm × (4.58 ± 0.49) μm (n = 50). These characteristics were similar to the descriptions of C. siamense (Weir et al. 2012). Gene sequences of isolates pxs6 and pxs7, including the internal transcribed spacer (ITS) region, actin (ACT), calmodulin (CAL), chitin synthase (CHS-1), glyceraldehyde-3-phosphate dehydrogenase (GAPDH), and β-tubulin 2 (TUB2), were successfully amplified and sequenced. All sequences were submitted to GenBank (accession numbers: ITS - PQ686314, PV125262, ACT - PQ757334, PV166234, CAL - PQ757335, PV166235, CHS-1 - PQ757336, PV166236, GAPDH - PQ757337, PV166237, TUB2 - PQ757338, PV166238) and blasted showed over 99% identity to C. siamense. Maximum Likelihood (ML) phylogenetic analysis was conducted using RAxML version 8.2.10 based on concatenated sequences (ITS, ACT, CAL, CHS-1, GAPDH, and TUB2), revealing that all isolates clustered with C. siamense (the type strain CBS 125378). To confirm pathogenicity, 10 μL of a conidial suspension (10 conidia/mL) of isolates pxs6 and pxs7 were inoculated onto six healthy leaves wounded with sterilized toothpicks of one-year-old M. oleifera seedlings, respectively. Control leaves were inoculated with sterile distilled water. All seedlings were covered with plastic bags to maintain high humidity in a 28°C greenhouse. After 5 days, anthracnose symptoms were observed on inoculated leaves, whereas control leaves were symptomless. C. siamense was successfully reisolated only from symptomatic leaves, fulfilling Koch's postulates. Botryosphaeria fabicerciana has been reported to cause leaf spot on Malania oleifera in China. This is the first report of C. siamense causing anthracnose on Malania oleifera in China (Pan et al. 2022). The results will provide crucial information for preventing and controlling anthracnose related to Malania oleifera.